Off-task social media multitasking during class: determining factors and mediating mechanism - Deng, Liping; Zhou, Yujie; Hu, Qingchun (International Journal of Educational Technology in Higher Education, 2022)
Framed by social learning theory, the study examines a set of personal and social factors determining off-task social media multitasking inside university classrooms. We aim to clarify the relationships between social media multitasking and self-efficacy, intrinsic motivation, multitasking preference as well as peer distraction, and to elucidate the interactive relationships between these factors. Questionnaire data from 203 university students in China show that academic self-efficacy fully mediates the association between intrinsic motivation and off-task multitasking. Moreover, multitasking preference partially mediates the association between peer distraction and off-task multitasking during class time. The findings of the study contribute to a deeper understanding of why students multitask during class, which can inform the development of strategies for combating social media distraction and enhancing students’ learning engagement.